Influencing factors and measures of water drive oilfield development effect - Gao Hang (E3S Web of Conferences, 2023)
Oil field is a very important non-renewable resource in China, which plays a very important role in economic strategy. In the process of oil field development, water flooding technology can effectively improve the production quality, provide a strong technical support for our oil field exploitation, and help to promote the sustainable development of oil field enterprises. However, there are many influencing factors in the exploitation process of water flooding oilfield, so the workers need to deeply explore the root cause of the problem from different angles and all aspects, and take scientific and reasonable countermeasures to improve the exploitation effect of water flooding oilfield. This paper mainly introduces the factors affecting the development effect of water flooding oilfield and puts forward the corresponding solutions. At the same time, combined with practical cases, the measures to improve the development effect of water flooding oilfield are analyzed in detail.